Isolation and characterization of yeasts from brazilian coffee beans for brewing application - Siqueira, Tatiane de Paula (2023)
The use of new non-Saccharomyces yeasts is a strategy for obtaining beers with new sensory profiles. This makes it possible to attend to the expectations of consumers who are increasingly looking for innovative beverages. In this study, we proposed the isolation of yeasts from coffee fruits, samples that have a wide range of microbial diversity. The study was conducted on samples obtained from the Alto da Mogiana region, a place in Minas Gerais known for its high-quality coffees. Twenty-seven isolates were obtained and of these, 52 % were able to use maltose as a carbon source and 87.5 % exhibited low hydrogen sulphide production. In addition, most of the isolates exhibited tolerance to factors such as alcohol content, low pH and temperature variation. Based on these results, two isolates (F702 and F605) were identified and selected for laboratory-scale fermentation characterization. Isolate F605 belongs to the Wickerhamomyces anomalus species, while F702 is a strain of Torulaspora delbrueckii. Laboratory fermentation trials have shown that these yeasts are unable to attenuate beer wort and, consequently, do not produce ethanol. In this context, the use of isolate F605 in co-fermentation with a conventional yeast was proposed. The F605 isolate was selected because of the better sensory profile observed throughout the experiments. The beer produced had an alcohol content of 5.6 %, indicating that the conventional yeast was able to grow and ferment in the presence of the isolate. An assay was also carried out to check consumer acceptance, which showed positive evaluations for criteria such as appearance and aroma. It can therefore be concluded that the coffee fruits evaluated were promising environments for isolating yeast with potential for application in the brewing industry. This reinforces the importance of sustainably exploiting Brazilian environments to obtain new national brewing strains, which can generate financial returns for the economy, as well as scientific and technological advances.